A mamoa 1 do Castelo (Jou) – Murça (Trás-os-Montes) : resultados dos trabalhos de escavação e de restauro dum dólmen de vestíbulo - Sanches, Maria de Jesus; Nunes, Susana Andreia; Silva, Margarida Santos (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
Results from excavation work carried out at Mamoa do Castelo (Trás-os-Montes, North-eastern Portugal) in 2000-2001, are presented here. This is a megalithic monument, with chamber and other access structures - corridor opened directly in the clayey sediments, antechamber – in connexion with a covering sub-circular mound. Special emphasis is given to the different phases of construction / use / “closure” during the 4th millennium / first half of 3rd millennium BC. The intentional and constant use of fire is also pointed out. This may have a ritual significance. Attention is drawn to the engravings found on the inner orthostats.